Bee venom acupuncture for rheumatoid arthritis: a systematic review protocol. Issue 4 (23rd April 2014) - Lee, Ju Ah; Son, Mi Ju; Choi, Jiae; Yun, Kyung-Jin; Jun, Ji Hee; Lee, Myeong Soo
Abstract : Introduction: This systematic review aims to analyse the trial data on the effects of bee venom acupuncture (BVA) for rheumatoid arthritis (RA). Methods and analysis: The following 14 databases will be searched from their inception to March 2014: MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials (CENTRAL), AMED, CINAHL, six Korean medical databases (OASIS, Korean Traditional Knowledge Portal, Korean Studies Information Service System, KoreaMed, Korean Medical Database and DBPIA) and three Chinese databases including CNKI (China National Knowledge Infrastructure), Wanfang and VIP. The methodological quality will be assessed using the Cochrane risk of bias tool. Dissemination: The systematic review will be published in a peer-reviewed journal. The review will also be disseminated electronically and in print. Trial registration number: PROSPERO 2013: CRD42013005853